Association of WT1 IgG antibody against WT1 peptide with prolonged survival in glioblastoma multiforme patients vaccinated with WT1 peptide. Issue 6 (31st May 2016) - Oji, Yusuke; Hashimoto, Naoya; Tsuboi, Akihiro; Murakami, Yui; Iwai, Miki; Kagawa, Naoki; Chiba, Yasuyoshi; Izumoto, Shuichi; Elisseeva, Olga; Ichinohasama, Ryo; Sakamoto, Junichi; Morita, Satoshi; et al.
Abstract : We previously evaluated Wilms' tumor gene 1 (WT1) peptide vaccination in a large number of patients with leukemia or solid tumors and have reported that HLA‐A*24:02 restricted, 9‐mer WT1‐235 peptide (CYTWNQMNL) vaccine induces cellular immune responses and elicits WT1‐235‐specific cytotoxic T lymphocytes (CTLs). However, whether this vaccine induces humoral immune responses to produce WT1 antibody remains unknown. Thus, we measured IgG antibody levels against the WT1‐235 peptide (WT1‐235 IgG antibody) in patients with glioblastoma multiforme (GBM) receiving the WT1 peptide vaccine. The WT1‐235 IgG antibody, which was undetectable before vaccination, became detectable in 30 (50.8%) of a total of 59 patients during 3 months of WT1 peptide vaccination. The dominant WT1‐235 IgG antibody subclass was Th1‐type, IgG1 and IgG3 . WT1‐235 IgG antibody production was significantly and positively correlated with both progression‐free survival (PFS) and overall survival (OS). Importantly, the combination of WT1‐235 IgG antibody production and positive delayed type‐hypersensitivity (DTH) to the WT1‐235 peptide was a better prognostic marker for long‐term OS than either parameter alone. These results suggested that WT1‐235 peptide vaccination induces not only WT1‐235‐specific CTLs as previously described but also WT1‐235‐specific humoral immune responses associated with antitumor cellular immune response. Our results indicate that the WT1 IgG antibody against the WT1 peptide may be a useful predictive marker, with better predictive performance in combination with DTH to WT1 peptide, and provide a new insight into the antitumor immune response induction in WT1 peptide vaccine‐treated patients. Abstract : What's new? The Wilms' tumor gene 1 (WT1) antigen is a promising target for immunotherapeutic strategies against glioblastoma multiforme (GBM), a brain tumor with poor survival rates. The present study shows that vaccination with WT1‐235 peptide can induce WT1‐235‐specific humoral immune responses in GBM patients. WT1‐235 IgG antibody production was significantly associated with prolonged progression‐free survival and overall survival. Survival times were significantly longer in GBM patients with positive delayed‐type hypersensitivity (DTH) responses to WT1 peptide. Thus, in WT1 vaccine‐treated GBM patients, especially those exhibiting positive DTH responses, WT1‐235 IgG antibody production can predict long‐term survival.